The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00406-014-0500-1
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality in the prospective Zurich study: prevalence, risk factors and gender

Abstract: Our prospective Zurich study found that suicidal ideation had occurred in 40.5 % and suicide attempts in 6.6 % of the population by age 50. Important gender differences were found in both suicidality and its risk factors. Suicide attempts were earlier and more frequent among women than among men: 70 versus 44 % reported their first suicide attempt before 20. For women, the relative risk of suicide attempts was 1.6, but the relative risk of suicidal ideation was about equal (1.1 for women). The main risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 45 publications
(48 reference statements)
1
16
1
1
Order By: Relevance
“…A consistent pattern of parasuicidal behaviour has previously been found in women and has been suggested to be due to the presence of affective symptoms, self‐esteem or even level of insight . Furthermore, women have been shown to attempt suicide at an earlier age than men, which fits with the gender difference in our young adult sample. In spite of referral to EIS, men were still more violent against others than women during the first year of EIS care.…”
Section: Discussionsupporting
confidence: 88%
“…A consistent pattern of parasuicidal behaviour has previously been found in women and has been suggested to be due to the presence of affective symptoms, self‐esteem or even level of insight . Furthermore, women have been shown to attempt suicide at an earlier age than men, which fits with the gender difference in our young adult sample. In spite of referral to EIS, men were still more violent against others than women during the first year of EIS care.…”
Section: Discussionsupporting
confidence: 88%
“…Contrary to several previous studies [9,16,43,44], sexual abuse was not associated with suicide risk in the present study. However, in a prospective cohort of street youth, it was found that physical abuse, emotional abuse, and emotional neglect, but not sexual abuse, associated with suicide attempts in adjusted analyses [45].…”
Section: Childhood Adversitiescontrasting
confidence: 99%
“…In non-Indigenous samples, sex differences have been reported in relation to the links between various types of childhood adversity and mental health outcomes in adulthood. 43,44 However, in some studies suicidality was more likely to be associated with childhood environmental risk factors in females, 45 whereas in other studies a greater association occurred in males. 46 Cultural factors and the local context also moderate the influence of sex on various health and social outcomes, 5,6 and may explain some of these disparate results across populations.…”
Section: Discussionmentioning
confidence: 99%